Generalized lymphoma, associated with HIV infection - Z. A. Khokhlova; R. A. Gileva; T. V. Sereda; N. A. Nikolaeva; A. P. Tishkina; L. Yu. Zolotuhina; Yu. M. Kirillova (Лечащий Врач, 2021)
The article gives a description of lymphoma in HIV infection. Our own observations of cases of diffuse B-cells lymphoma diagnosed at the late stages of HIV infection are presented. There is a variety of clinical manifestations and localization of the process, difficulties in diagnosis when combined with other AIDS-indicating diseases.